PENETAPAN TARIF RETRIBUSI PARKIR PADA PUSAT HIBURAN BEACHWALK DI KABUPATEN BADUNG - Rizky Ramadhon, Ariz; Dawisni Manik Pinatih, SLP (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
This paper entitled "Fixing Parking Retribution on Beachwalk Entertainment Center in Badung". Retribution is a retribution made by the Government to the person or legal entity as a source of regional revenue. There are three types of retribution that public service charges, retribution for services, and certain licensing retribution. Retribution is set in the Act-Law No. 28 Year 2009 on Regional Taxes and Retribution and Regional Regulation No. 5 of 2011 About Retribution Determination of Special Parking retribution rates should be held based on the applicable laws and regulations. The research method used in this paper is the normative legal research, research based on the rule of law and regulations. In this study, the raised issue is how regulation of retribution and whether price retribution on Beachwalk entertainment center in the district has been delinquent in accordance with the laws and regulations. The results and conclusions obtained namely that the setting of the Retribution in Regulation No. 28 Year 2009 on Regional Taxes and Retribution and Regional Regulation No. 5 of 2011 About Special Parking Lot Retribution and setting parking charges on Beachwalk in Badung doesn't follow the regulation because Beachwalk used per/hour price for parking that contradictive with Regional Regulation No. 5 of 2011 article 8.
Keywords: Retribution, Retribution Type, Price Fixing, Regulatory - Invitation